If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 5t = -12 + -3t Solving 36 + 5t = -12 + -3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3t' to each side of the equation. 36 + 5t + 3t = -12 + -3t + 3t Combine like terms: 5t + 3t = 8t 36 + 8t = -12 + -3t + 3t Combine like terms: -3t + 3t = 0 36 + 8t = -12 + 0 36 + 8t = -12 Add '-36' to each side of the equation. 36 + -36 + 8t = -12 + -36 Combine like terms: 36 + -36 = 0 0 + 8t = -12 + -36 8t = -12 + -36 Combine like terms: -12 + -36 = -48 8t = -48 Divide each side by '8'. t = -6 Simplifying t = -6
| 5n-8=4n+2n | | g(c+1)=x+4 | | 2(x+3)+3x=-3(x-2)+8x | | 9.2x-18.4=8.9x-53.4 | | f(x)=6x^2+78 | | -72x=20x+92 | | 26=-68x+42x | | 6v^2-11v-35=0 | | 3a-4b+c-d=0 | | ln(x+6)+ln(x+5)=ln(5) | | f(x)=2x^4-x^3+49x^2-25x-25 | | n-1.4n-1=6(n-2.3) | | C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 | | R+4=12 | | 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 |